Credit default swaps and firms' financing policies - Fuller, Kathleen P.; Yildiz, Serhat; Uymaz, Yurtsev (Journal of Corporate Finance, 2018)
This paper examines the impact of credit default swaps (CDS) on firms' financing and trade credit policies. Our results indicate firms with CDS trading on their debt increase their equity issuances. Further, firms with CDS trading on their debt and high levels of long-term debt issuances decrease their debt financing. Total and idiosyncratic risks are also higher for firms with CDS trading on their debt. These firms pay their suppliers and collect from their customers quicker. Thus, the impacts of the CDS market are not limited to the borrowing firms but also affect economically connected firms.